2019
DOI: 10.1111/all.14004
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of human mast cell progenitors in the bone marrow

Abstract: Bifidobacterium longum MM-2) improve rhinoconjunctivitis-specific quality of life in individuals with seasonal allergies: a double-blind, placebo-controlled, randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…However, allergen sensitization and challenge induce accumulation of mast cells in the airways 7‐9 . The increase in lung mast cells in such models is dependent on the recruitment and maturation of mast cell progenitors (MCp) from blood to the lung, 10 and a similar MCp population is found in humans 11,12 . To understand what features of allergic asthma that are due to mast cells, mouse strains lacking mast cells due to loss of kit were used, and demonstrated conflicting results 7,13‐15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, allergen sensitization and challenge induce accumulation of mast cells in the airways 7‐9 . The increase in lung mast cells in such models is dependent on the recruitment and maturation of mast cell progenitors (MCp) from blood to the lung, 10 and a similar MCp population is found in humans 11,12 . To understand what features of allergic asthma that are due to mast cells, mouse strains lacking mast cells due to loss of kit were used, and demonstrated conflicting results 7,13‐15 .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] The increase in lung mast cells in such models is dependent on the recruitment and maturation of mast cell progenitors (MCp) from blood to the lung, 10 and a similar MCp population is found in humans. 11,12 To understand what features of allergic asthma that are due to mast cells, mouse strains lacking mast cells due to loss of kit were used, and demonstrated conflicting results. 7,[13][14][15] Moreover, the observed phenotypes were often not due to loss of mast cells.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described a rare population of human MCp in the peripheral blood and bone marrow (3,4). Here, human MCp from blood and bone marrow were analyzed for their possible expression of CCR1 and CCR5.…”
Section: Human Mcp Demonstrate Surface Expression Of Ccr1 and Ccr5mentioning
confidence: 99%
“…In adult mice, mast cells seem to have a dual origin with long-lived connective tissue type mast cells mainly originating from yolk sac-derived mast cell progenitors (MCp), and mucosal mast cells developing from bone marrow-derived MCp that originate from fetal hematopoietic stem cells (2). In humans, a MCp population is present in peripheral blood and bone marrow (3,4). Mouse and human MCp are extremely rare, corresponding to ∼0.005% of blood mononuclear cells (5).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that MFC is a highly sensitive method for detecting and enumerating MCs in the bone marrow (BM), even in samples with very low MC percentage (Sánchez‐Muñoz, Teodosio, Morgado, & Escribano, 2011; Sánchez‐Muñoz, et al, 2014). It has been documented that in the bone marrow, MCs differentiate from the lineage‐specific markers negative (Lin − ), CD34 + , CD38 + , CD117 (c‐KIT) + and HLADR −/+ common myeloid progenitors (CMPs) (Dahlin & Hallgren, 2015; Salomonsson & Ungerstedt, 2020; Schmetzer, Valentin, Church, Maurer, & Siebenhaar, 2016). The MC precursors (immature MCs) differentiating from the CMPs show CD117 +++ , CD34 +/− , CD38 +/− , CD203 −/+ , CD33 ++ , CD45 + HLADR +/− , and tryptase −/+ expression (Escribano et al, 1998; Sánchez‐Muñoz et al, 2011; Teodosio, Garcia‐Montero, Jara‐Acevedo, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%